A novel adaptive bit loading algorithm for BICM-OFDM system - Wang Hao; Yang Hongwen; Tian Jun (2012 8th International Wireless Communications and Mobile Computing Conference (IWCMC), 2012)
In this paper, we present a bit-loading scheme for coded OFDM systems. In the proposed scheme, the subcarriers with multilevel modulation are decomposed into multiple binary equivalent channels each with an effective bit-level signal-to-noise ratios (SNR) depending only on the symbol-level SNR and the bit position. Thus, the problem of allocating bits among subcarriers has been converted to simply selecting the best binary channels. Simulation results have verified the superior performance to the classical algorithm.